Global Patterns in Net Primary Production Allocation Regulated by Environmental Conditions and Forest Stand Age: A Model‐Data Comparison. Issue 7 (13th July 2019) - Xia, Jiangzhou; Yuan, Wenping; Lienert, Sebastian; Joos, Fortunat; Ciais, Philippe; Viovy, Nicolas; Wang, Ying‐ping; Wang, Xufeng; Zhang, Haicheng; Chen, Yang; Tian, Xiangjun
Abstract: The allocation of net primary production (NPP) to different plant structures, such as leaves, wood, and fine roots, plays an important role in the terrestrial carbon cycle. However, the biogeographical patterns of NPP allocation are not well understood. We constructed a global database of forest NPP to investigate the observed spatial patterns of forest NPP allocation, as influenced by environmental drivers and forest stand age. We then examined whether dynamic global vegetation models (DGVMs) could capture these allocation patterns. The NPP allocation response to variations in temperature or precipitation was often opposite in leaves and fine roots, a finding consistent with the functional balance theory for allocation. The observed allocation to fine roots decreased with increasing temperature and precipitation. The observed allocation to wood and leaves decreased with forest stand age. The simulated allocation with five DGVMs was compared with the observations. The five models captured the spatial gradient of lower allocation to fine roots with increasing temperature and precipitation but did not capture coincident gradients in allocation to wood and leaves. None of the five models adequately represented the changes in allocation with forest stand age. Specifically, the models did not reproduce the decrease in allocation to wood and leaves and the increase in allocation to fine roots with increasing forest stand age. An accurate simulation of NPP allocation requires more realistic representation of multiple processes that are closely related to allocation. The NPP allocation database can be used to develop DGVMs. Key Points: The observed fine root allocation decreased with increasing temperature and precipitation, but leaf allocation showed an opposite change The observed wood and leaf allocation decreased with increasing forest stand age, but fine root allocation showed an opposite change Terrestrial biosphere models cannot completely reproduce the observed biogeographical patterns of NPP allocation in forest ecosystems